Academic Remunerations and Careers in Europe: Challenges in Attracting Talent - Civera, Alice; Lehmann, Erik; Meoli, Michele; Paleari, Stefano (International Higher Education, 2024)
In 2022, the Conference of Italian University Rectors commissioned a study on the attractiveness of European university systems. The main concern was the lack of competitiveness in terms of academic remuneration in Italy. Four European countries were selected for a comparative analysis: France, Germany, Italy, and the United Kingdom. Findings revealed that remuneration schemes and levels diverge significantly, and Italy lags far behind the other nations.